Variation and ontogeny of Calycoceras (Proeucalycoceras) canitaurinum (Haas, 1949) from the Upper Cretaceous (Cenomanian) of the Western Interior of the United States - Cobban, W; Kennedy, W (1990)
Mantelliceras canitaurinum Haas, 1949 was originally described from the basal part of the Cody Shale near Greybull, Wyo. The species, which belongs to the genus Calycoceras Hyatt, 1900, subgenus Proeucalycoceras Thomel, 1972, shows considerable variation. This upper Cenomanian index fossil is known from north-central Montana south to southwestern New Mexico and possibly to Trans-Pecos Texas. -Authors